INTERPRETASI GRAMATIKAL TEKS HYMNE MASSOMBA TEDONG DALAM SASTRA TORAJA: KAJIAN HERMENEUTIK SCHLEIERMACHER - Lilis Kanuna Embatau; Muhammad Rapi; Nensilianti Nensilianti (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2023)
Text of the Hymn Massomba Tedong in Toraja Literature: Schleiermacher's Hermeneutic Study.This study aims to describe the meaning of the text of Massomba Tedong using Schleiermacher's hermeneutic study. This type of research is descriptive qualitative. The data in this study are words or phrases in an array or hymn stanza. The source of this research is the book Passomba Tedong by Moses Eppang, et al (1990). The results showed that Schleiermacher's hermeneutical theory with its two interpretations, namely grammatical interpretation and psychological interpretation of the text of the hymn Massomba Tedong proves that the text of the hymn Massomba Tedong must be preserved for its wisdom because of the philosophical meaning contained by the text of the hymn Massomba Tedong of the Toraja people.